A Theoretical and Practical Evaluation of Struvite Control and Recovery. (1st August 2013) - Sharp, Robert; Vadiveloo, Enrique; Fergen, Robert; Moncholi, Manuel; Pitt, Paul; Wankmuller, David; Latimer, Ron
ABSTRACT: : Struvite accumulation is a costly problem in many water resource recovery facilities (WRRFs) that use anaerobic digestion, causing significant labor and equipment costs and potentially impacting facility performance and permit compliance. A comprehensive study was undertaken to evaluate possible solutions to struvite control at two similar Miami–Dade County, Florida, WRRFs. Alternatives analyzed included periodic cleaning and repair of damaged piping and equipment; optimum ferric salt dosing, use of in situ scaling coupons; and engineered struvite precipitation. The effectiveness and cost of each alternative was evaluated using a newly constructed dynamic process model and a net present worth analysis. Results indicate that nutrient recovery was a potential benefit at both facilities. This study establishes a comprehensive process and specific testing protocols for evaluating struvite control alternatives.